WEBSITE APPLICATIONS MOTOGP RACER USING MACROMEDIA DREAMWEAVER MX - Fahrudin Fitriadi; Cut Asiana Gemawaty, SKom, MMSI Cut Asiana Gemawaty, SKom, MMSI (Jurnal Sistem Informasi, 2008)
Advances in technology are growing rapidly encourage people to get informationquickly and up to date (the latest), especially facilities that began ogled as a media orpromotional information quickly accessible and interesting enough for the latest newsor current search. This method is considered very successful in meeting the needs forany information or promotions.To the writer want GP to provide information about motor racing fans who want tosee the idol of MotoGP racing and to promote what it is MotoGP. The site is expectedto provide flexibility for MotoGP fans and who want to know what it is MotoGP.